Application of Hindu Religious Education Values And Efforts to Improve the Quality of Hindu Human Resources (Study of Hindu Philosophy) - I Ketut Subagiasta; Ni Wayan Gateri (IAHN-TP Palangka Raya, 2022)
This paper aims to find out how the application of Hindu religious education values ??is very important given to students through educated efforts on the family line, formal channels at school, in the community, and on various occasions, so that students have broad insight, have the ability, have skills and experience. The application of Hindu religious education values ??is important given to students through educated efforts in the family line, formal channels at school, in the community, and on various occasions, so that students have broad insight, have abilities, have skills and experience. Knowledge is important to master, but important skills are also possessed so that there is a synergy between theory and practice. With efforts to improve the quality of Hindu human resources, it is hoped that the younger generation of Hindus can be competitive in the world of work.